Levy type Fourier analysis of thick cross-ply doubly curved panels - Oktem, Ahmet Sinan; Chaudhuri, Reaz A. (ELSEVIER SCI LTD, 2007)
A hitherto unavailable Levy type analytical solution to the problem of deformation of a finite-dimensional general cross-ply thick doubly curved panel of rectangular plan-form, modeled using a higher order shear deformation theory (HSDT), is presented. A solution methodology, based on a boundary-discontinuous generalized double Fourier series approach is used to solve a system of five highly coupled linear partial differential equations, generated by the HSDT-based general cross-ply shell analysis, with the SS2-type simply supported boundary condition prescribed on two opposite edges, while the remaining two edges are subjected to the SS3-type constraint. The numerical accuracy of the solution is ascertained by studying the convergence characteristics of deflections and moments of a moderately thick cross-ply spherical panel. Hitherto unavailable important numerical results presented include sensitivity of the predicted response quantities of interest to lamination, lamina material property, and thickness and curvature effects, as well as their interactions. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: thick laminate; higher order shear deformation theory (HSDT); doubly curved panel; spherical shell; cylindrical shell; cross-ply; analytical solution; boundary discontinuous double Fourier series; boundary constraints; BOUNDARY-VALUE-PROBLEMS; FREQUENCY-RESPONSE; LAMINATED SHELL; FREE-VIBRATION; ELEMENT; PDES; Mechanics; Materials Science